Tuning hexagonal NaYbF4 nanocrystals down to sub-10 nm for enhanced photon upconversion. Issue 36 (8th September 2017) - Shi, Ruikai; Ling, Xincan; Li, Xiaona; Zhang, Lu; Lu, Min; Xie, Xiaoji; Huang, Ling; Huang, Wei
Abstract : Controlled synthesis of sub-10 nm hexagonal NaYbF4 upconversion nanocrystals with enhanced upconversion emission was facilely achieved. Abstract : Enhancing upconversion emission is critical for small-sized lanthanide doped upconversion nanocrystals. A promising way is increasing the doping concentration of excitation energy absorbers, the Yb 3+ sensitizer. However, it is still a challenge to obtain small-sized hexagonal NaLnF4 (Ln: lanthanide) upconversion nanocrystals with a high Yb 3+ concentration due to the fast growth of NaYbF4 crystals, which hinders their applications particularly in biology. We here demonstrate a highly repeatable and controllable method for tuning the size of hexagonal NaYbF4 nanocrystals, down to ∼7 nm, without the assistance of additional impurity doping. By monitoring the reaction process, we found that ultrasmall hexagonal NaYbF4 nanocrystals were formed through an in situ transformation of their cubic counterparts. We observed an enhanced upconversion emission of NaYbF4 :Tm nanocrystals when compared to that of NaYbF4 :Y/Tm nanocrystals with less Yb 3+ doping. After coating a thin layer of a NaYF4 shell on NaYbF4 :Tm nanocrystals, a ∼100 times upconversion emission enhancement with over 800 times stronger emission in the ultraviolet and blue ranges was observed. This versatile method, together with the strong upconversion emission of the as-prepared ultrasmall nanocrystals, should facilitate the future applications of upconversion nanocrystals.